Effectiveness of Islamic Monetary Policy Transmission on Inflation and Economic Performance - Anton Bawono; Khoir Umi Laksana; Rifda Nabila; Risdiana Himmati (Universitas Islam Negeri Raden Mas Said Surakarta, 2021)
The most crucial part for the economic development of a country is maintaining the stability of inflation to create a positive climate for economic and business activities. A number of efforts can be performed to achieve stable inflation and increase economic growth by designing monetary policy incorporating the variables of Bank Indonesia Sharia Certificate (SBIS), Islamic Interbank Money Market (IIMM), and Financing. Drawing on this issue, the in-hand study aims to examine the effectiveness of Islamic monetary policy transmission, using the instruments of SBIS, IIMM, and Financing, on inflation and economic performance (GDP) from the period of January 2011 to December 2020. Using secondary data, this study employs VAR/VECM approach by the assistance of Eviews program. The results reveal that in the short term period, inflation is significantly influenced by the IIMM, while GDP t is affected by the GDP t-1 and financing activities. In the long term period, both inflation and GDP are determined by SBIS and financing activities. In general, this study results in a conclusion that the variables of IIMM, financing activities, and GDP t-1 influence the economic performance both in short and long term periods. These results contribute as fruitful insights to developing financial strategies and monetary policy to maintain stable inflation and improve economic performance of a country.